1999
DOI: 10.3109/10428199909050962
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmunity in Waldenstrom's Macroglobulinaemia

Abstract: Fifty-seven consecutive patients with Waldenström's Macroglobuliemia were studied retrospectively for autoimmune manifestations. 28 patients or 51% (16 women and 13 men) had clinical and/or serological autoimmune manifestations, two or more of these being concomitant in 20 (12 women and 8 men). The predominant findings were Coombs' positive autoimmune hemolytic anemia (16%), seropositive rheumatoid arthritis (16%), inflammatory gastric ulcer with parietal cell autoantibodies (12%), and IgM-cardiolipin syndrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 15 publications
0
16
0
2
Order By: Relevance
“…The prevalence of ITP in lymphoma studies was 0/92 in myeloma, 8 4% in MZL (54), 1.2% in follicular lymphomas (our department), 3.8-10% in makroglobulinemia, 10,28,55 and 9% in mantle cell lymphoma. 56 In T-cell lymphomas a prevalence of 11.1% 57 and in AILD prevalence of 24% 58,59 of thrombocytopenias was reported, but pathogenesis was not determined (Table 2 and 3).…”
mentioning
confidence: 54%
See 2 more Smart Citations
“…The prevalence of ITP in lymphoma studies was 0/92 in myeloma, 8 4% in MZL (54), 1.2% in follicular lymphomas (our department), 3.8-10% in makroglobulinemia, 10,28,55 and 9% in mantle cell lymphoma. 56 In T-cell lymphomas a prevalence of 11.1% 57 and in AILD prevalence of 24% 58,59 of thrombocytopenias was reported, but pathogenesis was not determined (Table 2 and 3).…”
mentioning
confidence: 54%
“…Among the hematologic autoimmune disorders, AIHA is more common than ITP while in CLL, AIHA was 3.3 times more common than ITP (8)(9)(10)(11). Both are less frequent in non-CLL-NHL and AIHA was only approximately twice as frequent as ITP (AIHA 1.57%, ITP 0.76%).…”
Section: -31449mentioning
confidence: 98%
See 1 more Smart Citation
“…In the absence of a molecular marker and due to the rarity of chromosomal abnormalities in ET, assays based on X-linked polymorphic markers in female patients were developed to investigate clonality. [1][2][3] We have previously shown that the simultaneous study of several marker genes using methylation and expressionbased assays associated to the study of both granulocytes and platelets provides the finest evaluation of clonality status of hematopoiesis. 1,2 Using X-chromosome inactivation patterns (XCIPs) analysis, several groups reported that circulating granulocytes and platelets derived from ET patients displayed a monoclonal pattern.…”
mentioning
confidence: 99%
“…1,2 Immunoglobulin G fragment C (Fcg)-mediated erythrophagocytosis has been recognized as the major pathogenic mechanism responsible for AIHA. 3,4 The clearance of immune complexes and the efficacy of their phagocytosis by splenic macrophages depend on the interactions between Fcg receptors (FcgR) and immunoglobulin G (IgG).…”
mentioning
confidence: 99%